Price Differences between Voting and Non-Voting Shares in Crisis and Boom - Niehoff, Karin; Laskowski, Piotr (Management international / International Management / Gestiòn Internacional, 2019)
When a company issues both voting and non-voting shares, the prices are usually different, due to the value of the voting right versus the preferred dividend of the non-voting share. This price difference may well be influenced by the business cycle. We analyze the price differences between voting and non-voting shares in Germany and Italy in different business cycles during the period 2003–2013, but find little influence attributable to the business cycle. However, the impact of the ownership structure and the market performance on the prices of voting and non-voting shares do differ in crisis and boom periods.